Data Analysis of Student Attitude Survey Based on Internet Analysis Technology - Cao, Yongcheng; Liu, Quanguo; Chen, Huajie (Bright Publisher, 2022)
Language attitude is people’s understanding and evaluation of languages, which has important effect on language learning. Based upon investigation into 605 tibetan college students from 5 colleges in Tibet areas, and combined with network data, this paper mainly analyses their attitude towards Tibetan, Chinese and English from four dimensions: recognizing, instrumental, integrative and transferring attitude. This paper also discusses the relationship between students’ language attitude and their gender and grade.